Implementasi E-Form 1771 dalam Pelaporan SPT Tahunan Badan CV XYZ Sebagai Wujud Kepatuhan Wajib Pajak (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study discusses the implementation of e-Form 1771 in the submission of the Annual Corporate Income Tax Return (SPT) by CV XYZ as a form of compliance with tax obligations. A qualitative descriptive method was employed in this research. Data were collected through interviews, direct observation, and examination of the published procedures for submitting the Annual Tax Return using e-Form 1771. The findings indicate that the use of the e-Form facilitates ease of reporting, saves time, and enhances data accuracy. The implementation of e-Form 1771 has proven to support CV XYZ’s tax compliance by ensuring timely fulfillment of tax obligations in accordance with the prevailing legal regulations for the relevant fiscal year.